Facebook/Instagram ban (Russia) - Voidly (2022)
CRITICAL severity censorship detected in Russia. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: RU-2022-0003
Keywords: censorship; RU; censorship; critical